KRITERIA ISTRI IDEAL “THE GOOD WIFE” DALAM MEMBENTUK KELUARGA MUSLIM GEN Z - Noor khalifah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This article aims to explore the criteria of an ideal wife from an Islamic perspective and its relevance for Generation Z in their efforts to form a strong Muslim family. The family is the main foundation for human character formation, where the wife's role is central in educating a virtuous generation. However, Generation Z, born between 1995 and 2010, faces significant challenges because they grew up in a digital era dominated by information technology and social media. Based on a study of the hadith of the Prophet Muhammad (peace be upon him), Islam establishes four main criteria for choosing a wife: wealth, lineage, beauty, and religion, with a primary emphasis on religious obedience (shalihah) as the key to success in this world and the hereafter. Through literature analysis and understanding the opinions of scholars such as Imam An-Nawawi, this study concludes that although individual ideals vary, religious obedience remains the single most fundamental indicator in facing the social and technological dynamics of the Gen Z era to create a sakinah, mawaddah, wa rahmah family.